Audit of Hemodialysis in Children Weighing Less than 20 kg in an African Pediatric Nephrology Unit. Issue 6 (30th July 2018) - Keenswijk, Werner; Sinclair, Gina; Benetton, Marian; du Plessis, Mandi; Nourse, Peter; Reddy, Deveshni; McCulloch, Mignon
Abstract: Peritoneal dialysis and kidney transplantation remain the preferred choices for renal replacement therapy in young children. These options, however, are not always feasible, and hemodialysis (HD) is therefore an accepted alternative. In small children presenting with end‐stage renal disease, HD presents several challenges and is often unavailable in lower‐ and middle‐income countries. To assess these challenges and outcomes of maintenance HD in young children, we performed an audit of children below 20 kg with end‐stage renal disease, receiving HD for ≥4 weeks, from 1 January 2008 to 31 July 2016 at the Red Cross War Memorial Children's Hospital. We identified 15 children weighing 6.8–18.5 kg (mean 12.9 kg ±3.5 SD) and aged 11.5–105 months (mean 52.2 months±4.2 SD) at HD initiation. Mean duration of HD was 11.8 months (range 1–61.5 months ± 16.9 SD). Seven children underwent successful transplantation, two patients died, and four currently still receive HD. Two patients, while on HD, relocated to other centers. An average of 2.6 (range 1–5) different vascular accesses was required per patient. Technical difficulties were the most common cause of central‐line removal (81%), while catheter‐associated bacteremia was 1.1/1000 catheter days. Frequent problems were intradialytic hypotension, growth stunting, and interdialytic hypertension. HD in lower‐ and middle‐income countries is feasible in small children but presents with certain challenges. Advocacy with lobbying for funding and development of "child‐friendly" dialysis equipment and specialized centers with highly skilled personnel are the cornerstones of successful pediatric HD programs in less‐resourced centers.